2016
DOI: 10.1007/s12122-016-9225-4
|View full text |Cite
|
Sign up to set email alerts
|

Individuals and Communities: the Importance of Neighbors Volunteering

Abstract: In this analysis, I examine the effects of community-level volunteering on an individual's choices regarding time -whether to work and whether to volunteer. In order to better explain the decision to volunteer, a classic pure public goods structure is contrasted with a less restrictive impure public goods model that admits other possible private motivations. The results of this study undermine the neoclassical notion that volunteering can be understood solely as a pure public good that is provided less when ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…S5 concludes that, contrary to H5, an altruistic culture in the country (causal condition 6) is a sufficient condition to assure group participation, even when employee involvement (causal condition 5) does not appear as a causal condition. From this solution, we can also infer that hotel groups imitate the prosocial behaviour of other groups in their area (Neymotin, 2016) even when there is no demand to do so from customers and employees. Moreover, this solution shows that 100% of cases come under the two types of capitalism found in S3 (six groups in USA, seven in UK, five in Canada, one in Australia, and one in Ireland).…”
Section: Why Hotel Groups Get Involved In Their Communitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…S5 concludes that, contrary to H5, an altruistic culture in the country (causal condition 6) is a sufficient condition to assure group participation, even when employee involvement (causal condition 5) does not appear as a causal condition. From this solution, we can also infer that hotel groups imitate the prosocial behaviour of other groups in their area (Neymotin, 2016) even when there is no demand to do so from customers and employees. Moreover, this solution shows that 100% of cases come under the two types of capitalism found in S3 (six groups in USA, seven in UK, five in Canada, one in Australia, and one in Ireland).…”
Section: Why Hotel Groups Get Involved In Their Communitiesmentioning
confidence: 96%
“…Along these lines, Ramasamy, Yeung, and Au The existence of social conventions could explain the relationship between altruism and culture in countries even when the focus is not religion. From this perspective, people imitate the prosocial behaviour of others (Nook, Ong, Morelli, Mitchell, & Zaki, 2016), resulting in similar behaviour in spatial and social proximities (Neymotin, 2016). This shared altruism might influence the behaviour of customers, employees and managers and, as a result, their involvement in communities.…”
Section: Hypothesesmentioning
confidence: 99%
“…Having contact with friends, for instance, appears to be a stronger predictor for actual and potential volunteering than older adults’ individual characteristics and resources (Dury et al, 2015). Likewise, being socially integrated increases the chances of being aware of volunteer opportunities or being asked to volunteer (Neymotin, 2016; Okun & Michel, 2006; Yörük, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…From a pure public goods perspective, one might think that a highly publicized disaster would tend to encourage individuals to do less volunteering, since it is clear in the case of such a large disaster that others will presumably be picking up the slack (Freeman, 1997;Samuelson, 1954). On the other hand, when a larger number of people are seen to volunteer in particular, it has been shown that individuals are more likely to also do so (Neymotin, 2016), whether from a desire for prestige, networking and relationships, or from increased warm glow effects (Andreoni, 1990;Harbaugh, 1998;Prouteau and Wolff, 2008). Thus, the initial a priori assumption regarding the direction of effects immediately resulting from a disaster like a hurricane is not obvious given these countervailing neoclassical and behavioral economic forces.…”
Section: Introductionmentioning
confidence: 99%